İç Savaştan Devlet Başkanlığı Seçimine: Liberya’da Kalıcı Barış ve İstikrar Ne Derece Mümkün? - Engin AVCI (Gazi Akademik Bakış)
Liberia, founded by emancipated slaves from the US in the 19th century, was relatively stabilized by the intervention of the ECOWAS and the UN in 2003 after the military coup in 1980 and the civil war in 1989. The United Nations Mission in Liberia (UNMIL) of which drawdown process was started after the responsibility of security taken over by Liberian government in 2016, was closed completely in 2018. The victory of George Weah in 2017 presidential election that was led under the full responsibility of Liberian government, has started a new era for Liberians. This article aims to examine the dynamics that lead Liberia to the civil war and to question whether a permanent peace and stability is possible after the presidential election and the closure of UNMIL. This research, based on the information gathered through open sources, shows thatthe political and socioeconomic dynamics leading the country to the civil war have not completely disappeared although the political profile of the country has changed historically, that the gaps in security sector reform still cause some risks, and finally that security in Liberia is still fragile in terms of national, regional and international developments.